2017
DOI: 10.1177/1010428317691740
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RNA-binding motif 10 is associated with advanced tumor stage and malignant behaviors of lung adenocarcinoma cancer cells

Abstract: This study assessed RNA-binding motif 10 expression in lung adenocarcinoma tissues and examined the role and mechanism of RNA-binding motif 10 in the regulation of lung adenocarcinoma malignancy. Lung adenocarcinoma and corresponding adjacent non-tumor lung tissues from 41 patients were subjected to reverse transcription-polymerase chain reaction and Western blot assessment to detect RNA-binding motif 10 expression. Recombinant lentivirus carrying RNA-binding motif 10 complementary DNA was used to infect lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Although RBM10 has been shown to control cancer cell proliferation by differentially regulating NUMB alternative splicing [11] and its expression is associated with advanced tumor stage [12], much more need to learn about its role in cancer development. In attempt to address this question, we first searched genomic and gene expression databases for RBM10 status.…”
Section: Overexpression Of Rbm10 Inhibits Cancer Cell Proliferation Amentioning
confidence: 99%
“…Although RBM10 has been shown to control cancer cell proliferation by differentially regulating NUMB alternative splicing [11] and its expression is associated with advanced tumor stage [12], much more need to learn about its role in cancer development. In attempt to address this question, we first searched genomic and gene expression databases for RBM10 status.…”
Section: Overexpression Of Rbm10 Inhibits Cancer Cell Proliferation Amentioning
confidence: 99%
“…There is substantial evidence pointing to the pro-survival and anti-apoptotic roles of BIRC3 in cancer cells; however, not all data are consistent ( Frazzi, 2021 ). An in vitro study showed that RNA-binding motif 10 overexpression inhibited the malignant behaviors of A549 and H1299 cells by inducing the expression of AKT2, BIRC3, and JUN ( Guan et al, 2017 ). However, Dubois et al (2019) reported that overexpression of BIRC3 regulated by RASSF1A depletion decreased the rate of cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 690 genes that were regulated by RBM10 expression in A549 cells were identified, of which 304 were up‐regulated and 386 were down‐regulated. Among these, RAP1A expression was the most down‐regulated (63.5%); thus, we explored its downstream signalling pathway. RAP1A is a type of Ras‐associated protein 1 (RAP1), with 95% sequence homology to RAP1B .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to explore the effect of RBM10 overexpression and knockdown on the proliferation of lung adenocarcinoma cells as well as the affected downstream pathways by assessing the expression of several regulatory proteins that have previously been identified as being modulated by RBM10 . We then sought to verify the effect of RBM10 overexpression and inhibition in vivo in BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%